In Search of Practices and Techniques to Developing Leadership Competency Model for Millennials in Energy Sector: A literature Review - Bently Nevada Tobing; Jann H. Tjakraatmadja; Donald C. Lantu; Henndy Ginting (Jurnal Manajemen Indonesia, 2023)
Leadership competency model has become critical as the emergence of millennials in energy sector and the business shifting to new era caused by VUCA and COVID-19 pandemic. To promoting and maintaining high-performing millennial employees and reduce the maturity gap compared to the Gen – X employees, there is needs to enrich the content and implementation process of leadership competency to meet current and future necessities. However, little is known about research related to competency models that exist in energy sector organizations, particularly for millennials.The purpose of this article is to review the literature on leadership competency models in various industries and work organizations with focus intention is on the energy sector. It will also examine competency model approaches used by undertaking a comparative analysis of practices and techniques when developing the leadership competency models. Findings suggested that 24 leadership competency model have been used in the literature obtained with very limited number of the implementation in energy sectore yet none has been done for millennials case. Most of the models reviewed are using interviews and surveys as the main approach. Behavioral Event Interview is very effective way to build new leadership competency model.Energy sector organizations can use the results to design their own management competency models. It can also be used by other researchers for possible future research. Keywords—Energy; Competency; Leadership; Millennials; Model